The Cretaceous Normal Superchron: A Mini-Review of Its Discovery, Short Reversal Events, Paleointensity, Paleosecular Variations, Paleoenvironment, Volcanism, and Mechanism - Yutaka Yoshimura (Frontiers in Earth Science, 2022)
The Cretaceous Normal Superchron (CNS) was first defined in the 1960s to explain the Cretaceous Quiet Zone in marine magnetic anomaly profiles, which includes no or fewer geomagnetic reversals. This ∼37 million years period is considered the most unique and extreme geomagnetic feature for the last 160 Myr. Superchrons may be caused by the geodynamo operating at peak efficiency with a unique heat flux at the core-mantle boundary (CMB). Previous studies suggest that the CNS is a sign of the connection between Earth’s interior and surface. During the CNS, the geomagnetic intensity may have fluctuated significantly, and the average may have changed with time, and the paleosecular variations had unique features. The warm climate around the CNS may have been caused by volcanic activity associated with active mantle convection. Such mantle convection increases heat flux at the CMB during the CNS, but geodynamo simulations predict small heat flux, which are inconsistent. This discrepancy may be resolved by the growth and collapse of a superplume or by an increase and decrease in the subduction flux.